The pace pattern of the men`s 1500 m race with different levels - Yang, Y.; Enomoto, Y. (Journal of Physical Education and Sport, 2022)
This study investigates the relationship between the speed in the men's 1500 m run at different levels and stride length, stride frequency, contact time, flight time and centre of mass (delta_y) and clarifies the relationship between pace pattern and performance among 1500 m runners by analysing the pace patterns in the official 1500 m running race with different performance levels. Twenty-one male 1500 m runners in official competitions were videotaped with video cameras at a 60-Hz sampling rate during the whole course of the race. The ratio of race time to personal records was never <98% for any runner who participated in this study. The average running speed, stride length, stride frequency, contact time, flight time and the centre of mass (delta_y) were calculated for every 100 m by reading the video frames. The main results were as follows: 1) High-performance runners tend to have high speed, fast stride frequency, long stride length, short contact time and flight time, and small fluctuations in centre of body gravity. A significant correlation was found between the running speed in each group and each variable. 2) From the results of the multiple regression analysis with the 1500 m race record as the independent variable and each quarter speed as the dependent variable, it is understood that the running speed in the middle stage had the greatest effect. 3) The pace patterns were classified into three types depending on the record level: "Up-down wave type," "even-fast type," and "fast-slow-fast type." This study examined the 1500 m pace pattern at different levels; the mechanical variables of runners at different levels have different effects on their speed. Controlling the middle-stage speed is essential to improve athletes' sports performance.